MODELING OF THREE-DIMENSIONAL SUBSURFACE STRUCTURES BASED ON GRAVITY ANOMALY IN SOUTHWEST SUMBA INDONESIA - Novitri, Adinda; Margiono, Relly; Pevriadi, Anggi; Zakariya, Hilmi; Segoro, Yan Adi (Indonesian Physical Review, 2025)
Modeling subsurface conditions using gravity anomaly data, focusing on density contrasts, provides critical insights into subsurface structures and supports identifying rock types. This study aims to define residual gravity anomalies in the Sumba region and utilize them to develop a three-dimensional subsurface model of Southwest Sumba, characterizing density contrasts and associated rock formations. Gravity data from the TOPEX dataset were employed in this research. The Airy isostasy model was applied to separate regional and residual anomalies, followed by a three-dimensional inversion using the Generalized Cross-Validation (GCV) method. The results reveal residual gravity anomalies range from -170 mGal to 211 mGal, with the Java Trench exhibiting the highest anomaly. The 3D modeling shows a relatively homogeneous density contrast at shallow depths, transitioning to more erratic variations at greater depths, extending to 15 km beneath Southwest Sumba Island. Furthermore, the calculated densities are consistent with the region's known geological background. The Java Trench, located south of Sumba, notably demonstrates a consistently high-density contrast from shallow to deeper depths, highlighting its tectonic complexity.